2007
DOI: 10.1038/sj.embor.7400935
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of arachidonic acid action on syntaxin–Munc18

Abstract: Syntaxin and Munc18 are, in tandem, essential for exocytosis in all eukaryotes. Recently, it was shown that Munc18 inhibition of neuronal syntaxin 1 can be overcome by arachidonic acid, indicating that this common second messenger acts to disrupt the syntaxin-Munc18 interaction. Here, we show that arachidonic acid can stimulate syntaxin 1 alone, indicating that it is syntaxin 1 that undergoes a structural change in the syntaxin 1-Munc18 complex. Arachidonic acid is incapable of dissociating Munc18 from syntaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 33 publications
2
86
0
Order By: Relevance
“…For example, titration studies demonstrated the ability of Munc18 to displace SNAP25 and VAMP2 from syntaxin 1, coordinate with the ability to co-immunoprecipitate only syntaxin 1 with anti-Munc18 antibody but not SNAP25 or VAMP2 from detergent-solubilized (1% Triton X-100) synaptosomal membranes (24,33,46). However, more recent studies show that although the Munc18-syntaxin binary complex does predominate, under in vitro conditions containing little (0.1% Triton X-100) or no detergent, SNARE complexes bound by Munc18 were detected (27,28,51,57). Using a novel immunofluorescent approach, it was shown that syntaxin 1 bound to Munc18-1 could also bind SNAP25 but that the addition of VAMP2 displaced Munc18-1 (39).…”
Section: Discussionmentioning
confidence: 94%
“…For example, titration studies demonstrated the ability of Munc18 to displace SNAP25 and VAMP2 from syntaxin 1, coordinate with the ability to co-immunoprecipitate only syntaxin 1 with anti-Munc18 antibody but not SNAP25 or VAMP2 from detergent-solubilized (1% Triton X-100) synaptosomal membranes (24,33,46). However, more recent studies show that although the Munc18-syntaxin binary complex does predominate, under in vitro conditions containing little (0.1% Triton X-100) or no detergent, SNARE complexes bound by Munc18 were detected (27,28,51,57). Using a novel immunofluorescent approach, it was shown that syntaxin 1 bound to Munc18-1 could also bind SNAP25 but that the addition of VAMP2 displaced Munc18-1 (39).…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports showed that cPLA 2 activity modifies the transport of several proteins between Golgi vesicles and plasma membranes in nonneuronal cell types (Choukroun et al, 2000;Regan-Klapisz et al, 2009). Taking this into account along with the role of AA in Munc18-syntaxin interactions (Connell et al, 2007) and the influence of cPLA 2 on membrane organization and lipid vesicles formation (Gubern et al, 2008), it is tempting to speculate that A␤-activated cPLA 2 1123.e25could surrogate the transportation of synaptic proteins into various lipid compartments.…”
Section: Discussionmentioning
confidence: 98%
“…The presynaptic proteins synaptophysin and synaptotagmin are involved in the formation of soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complexes with several other partners such as syntaxin-1 and Munc18. AA stabilizes interactions between Munc18, syntaxin-1 and synaptosomal-associated protein, 25 kDa (SNAP25), thus favoring exocytosis of neurotransmitters (Connell et al, 2007;Latham et al, 2007). Increase in free AA released by cPLA 2 in response to A␤ oligomers could therefore be involved in synaptic dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, depletion of the cPLA 2 product, arachidonic acid, has been shown to inhibit STX4 from forming SNARE complexes (Connell et al, 2007). Arachidonic acid induces the so-called 'syntaxin-opened' conformation that is required for SNARE assembly (Connell et al, 2007;Rickman and Davletov, 2005), further supporting the involvement of cPLA 2 in the modulation of syntaxins that participate in SNARE trafficking and assembly.…”
Section: Loss Of Npc1 Interferes With Cholesterol-sensitive Vesicle Fmentioning
confidence: 95%